Game time - Murphy, Stuart (New york : Harper collins, 2000)
Calendars and clock keep track passing time as the huskies prepare for and complete in the championship soccer against the falcons.
Keywords: Soccer - Fiction; Time - Fiction; Clocks and watches -- fiction